UV-VIS spectroscopy as a nondestructive and effective characterization tool for II-VI compounds - Oudhia, A (Recent Research in Science and Technology, 2012)
The characterization of size dependent optical properties of Group II-VI semiconductor particles provide a lot of qualitative and quantitative information about them like size, quantum yield, monodispersity, shape and presence of surface defects. Presently a review of UV-vis optical absorption spectroscopy is described for extracting useful information about these nanomaterials for the analysis of their optical properties with special reference to semiconducting quantum dots.